2011
DOI: 10.1021/ac2007224
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Barrier Discharge Molecular Emission Spectrometer as Multichannel GC Detector for Halohydrocarbons

Abstract: A novel microplasma molecular emission spectrometer based on an atmospheric pressure dielectric barrier discharge (DBD) is described and further used as a promising multichannel GC detector for halohydrocarbons. The plasma is generated in a DBD device consisting of an outer electrode (1.2 mm in diameter) and an inner electrode (1.7 mm in diameter) within a small quartz tube (3.0 mm i.d. × 5.0 mm o.d. × 50 mm), wherein analyte molecules are excited by the microplasma to generate molecular emission. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…A microplasma molecular emission spectrometer detector based on an atmospheric pressure DBD was described by Hou's group (66). This device was used as a multichannel GC detector for halohydrocarbons.…”
Section: Dielectric Barrier Discharge Microplasma Detectors the Use mentioning
confidence: 99%
“…A microplasma molecular emission spectrometer detector based on an atmospheric pressure DBD was described by Hou's group (66). This device was used as a multichannel GC detector for halohydrocarbons.…”
Section: Dielectric Barrier Discharge Microplasma Detectors the Use mentioning
confidence: 99%
“…The progress of gas chromatography mainly includes the miniaturization of instruments (Lee et al, 2008), the stationary phases (Gu and Yan, 2010), and detectors (Li et al, 2011). The application of new nanomaterials, sub-micromaterials, and functionalized recognition or affinity materials in the preparation of stationary phase or monolithic column is one of the most prominent progresses in this field.…”
Section: Chromatography and Micro/nanofluidic Analysismentioning
confidence: 99%
“…A DBD-based gas chromatography (GC) detector was thus developed. Li et al [16] reported MES based on the combination of DBD and charge coupled device (CCD) as a multi-channel GC detector for the detection of VOCs. Compared to the traditional elemental detectors such as MS or ICP-AES/MS, a DBD detector possesses some attractive characteristics such as multi-channel, fast respond and high sensitivity, but simplicity, low-cost in construction and maintenance, and compactness in instrumentation.…”
Section: Figurementioning
confidence: 99%